Efikasi terapi artemeter dan primakuin versus klorokuin pada anak-anak penderita malaria tanpa komplikasi di wilayah Puskesmas Kokap, Samigaluh, Girimulyo Kabupaten Kulon Progo. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Margareta Yuliani, Soeroyo Machfudz, Tonny Sadjimin - The efficacy of artemether and primaquin versus chloroquine-primaquine on uncomplicated malaria: A study on children in Kokap, Samigaluh area, and Girimulyo Puskesmas, Kulon Progo Background: Malaria is one of infectious diseases influencing mortality of newborns, infants, and delivering mothers. Chloroquine is a standard anti-malaria or fist-line antimalarial drug for treatment and chemoprophylaxis of susceptible uncomplicated malaria in Indonesia. Increased resistance toward standard medications turns out to be one of difficulties in malaria prevention, especially in endemic areas. To solve the problem, a new antimalaria drugs i.e. artemether is now under extensive studies. Objective: To know the efficacy of artemether-primaquine therapy compared to chloroquine-primaquine therapy in children with uncomplicated malaria. Methods: Sixty-three children were enrolled in this study through active case detection (ACD) and passive case detection (PCD) from April to July 2004 in Kokap, Samigaluh and Girimulyo Puskesmas, Kulon Progo